1992
DOI: 10.1105/tpc.4.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins and auxins control the expression of a gene in Nicotiana plumbaginifolia cells by feedback regulation.

Abstract: Both cytokinin (N6-benzyladenine [BA]) and auxin (2,4-dichlorophenoxyacetic acid [2,4-D]) stimulate the accumulation of an mRNA, represented by the cDNA pLS216, in Nicotiana plumbaginifolia suspension culture cells. The kinetics of RNA accumulation were different for the two hormones; however, the response to both was transient, and the magnitude of the response was dose dependent. Runoff transcription experiments demonstrated that the transient appearance of the RNA could be accounted for by feedback regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 46 publications
2
37
1
1
Order By: Relevance
“…All responses are also elicited by cytokinin treatment, albeit only in whole plants [38,39,40]. It appears that in the ice plant multiple stimuli trigger several stress-related responses, perhaps a general observation as similar results have been reported in tobacco for other inducible genes [13,25]. A comparison of plant gene expression, senescence and morphology during uninduced and induced cytokinin synthesis and salt stress may provide insights into the role of cytokinin in planta during various environmental and developmental processes.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…All responses are also elicited by cytokinin treatment, albeit only in whole plants [38,39,40]. It appears that in the ice plant multiple stimuli trigger several stress-related responses, perhaps a general observation as similar results have been reported in tobacco for other inducible genes [13,25]. A comparison of plant gene expression, senescence and morphology during uninduced and induced cytokinin synthesis and salt stress may provide insights into the role of cytokinin in planta during various environmental and developmental processes.…”
Section: Introductionmentioning
confidence: 80%
“…At the physiological level, salt stress, ABA and cytokinin can affect the stomatal response [6]. Correlations between osmotic stress, cytokinins, and flowering have also been established before [25,13]. Thus, senescence and antisenescence activities exerted by cytokinins are not clearly separated and likely depend not only on the absolute cytokinin amount, but also the cytokinin ratio with respect to other growth regulators (e.g.…”
Section: Cytokinin Senescence and Environmental Stressmentioning
confidence: 99%
“…One of the best characterized examples of cytokinin regulated genes is the pLS216 gene from Nicotiana plumbaginifolia [32]. This gene is a member of a family of environmentally responsive genes, and therefore has been renamed msrl, for mutliple stimulus response.…”
Section: Molecular Aspects Of Cytokinin Actionmentioning
confidence: 99%
“…These genes encode proteins related to the stringent starvation response protein from E. coli. Dominov et al [32] showed that the msrl mRNA accumulated in response to both cytokinin and auxin although the kinetics of accumulation differed for the two hormone treatments. The response to auxin peaked between 3-6 h, while the cytokinin response peaked in 24-48 h. In addition, cytokinin appeared to sensitize cells to subsequent auxin treatment.…”
Section: Molecular Aspects Of Cytokinin Actionmentioning
confidence: 99%
“…Together with independently isolated homologous proteins from soybean [10,22], potato [62], Nicotiana plumbaginifolia [12], and maize [60] they are members of a hitherto unidentified new type of plant GSTs [13]. GSTs are a ubiquitous family of proteins that catalyze the nucleophilic addition of the thiol of reduced glutathione to a large variety ofhydrophobic electrophiles (for reviews see [9,11,43,51,55]).…”
Section: Introductionmentioning
confidence: 99%